Excess Maternal Fructose Consumption Increases Fetal Loss and Impairs Endometrial Decidualization in Mice - Saben, Jessica L. (Endocrinology, 2016)
The most significant increase in metabolic syndrome over the previous decade occurred in women of reproductive age, which is alarming given that metabolic syndrome is associated with reproductive problems including subfertility and early pregnancy loss. Individuals with metabolic syndrome often consume excess fructose, and several studies have concluded that excess fructose intake contributes to metabolic syndrome development. Here, we examined the effects of increased fructose consumption on pregnancy outcomes in mice. Female mice fed a high-fructose diet (HFrD) for 6 weeks developed glucose intolerance and mild fatty liver but did not develop other prominent features of metabolic syndrome such as weight gain, hyperglycemia, and hyperinsulinemia. Upon mating, HFrD-exposed mice had lower pregnancy rates and smaller litters at midgestation than chow-fed controls. To explain this phenomenon, we performed artificial decidualization experiments and found that HFrD consumption impaired decidualization. This appeared to be due to decreased circulating progesterone as exogenous progesterone administration rescued decidualization. Furthermore, HFrD intake was associated with decreased bone morphogenetic protein 2 expression and signaling, both of which were restored by exogenous progesterone. Finally, expression of forkhead box O1 and superoxide dismutase 2 [Mn] proteins were decreased in the uteri of HFrD-fed mice, suggesting that HFrD consumption promotes a prooxidative environment in the endometrium. In summary, these data suggest that excess fructose consumption impairs murine fertility by decreasing steroid hormone synthesis and promoting an adverse uterine environment.